2020
DOI: 10.1111/aos.14517
|View full text |Cite
|
Sign up to set email alerts
|

Surgery as a safe and effective treatment option for spheno‐orbital meningioma: a systematic review and meta‐analysis of surgical techniques and outcomes

Abstract: Purpose The effectiveness and safety of surgery for spheno‐orbital meningiomas remains subject of debate, as studies often describe different surgical approaches and reconstruction techniques with very heterogeneous outcomes. We aimed to systematically summarize and analyse the literature on spheno‐orbital meningiomas regarding presenting symptoms, surgical techniques, outcomes and complications. Methods Studies were retrieved from eight databases. Original articles were included if in ≥5 patients presenting s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 51 publications
2
37
0
Order By: Relevance
“…There are many approaches for this tumor. As discussed in a recent meta-analysis,[ 8 ] the most used surgical technique was the pterional craniotomy associated or not orbital wall, anterior clinoid, and optic canal removal. [ 2 , 18 ] Since 2008, orbitotomy through supraciliary or trans-eyelid approach started to be used.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There are many approaches for this tumor. As discussed in a recent meta-analysis,[ 8 ] the most used surgical technique was the pterional craniotomy associated or not orbital wall, anterior clinoid, and optic canal removal. [ 2 , 18 ] Since 2008, orbitotomy through supraciliary or trans-eyelid approach started to be used.…”
Section: Discussionmentioning
confidence: 99%
“…In their meta-analysis, Fisher et al found a follow-up range between 3 and 135 months. [8] e same meta-analysis related improvement of 96% of the patients concerning diplopia and motility deficit after surgical resection, with hypesthesia of CNV as the most common postoperative complication. [8] is article aims to evaluate exophthalmos' improvement in a surgical series without orbital reconstruction and complications analysis.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…In our cohort, we observed a total of 10 patients with postoperative hypoesthesia in the region of the trigeminal nerve, which was significantly (p=0.0107) associated with GTR (Table 3). Other groups observed only sporadic trigeminal nerve deficits and other cranial nerve deficits (5,8,12,14,19,(24)(25)(26). This could be biased by the surgical experience of the surgeon and the aggression of the tumors.…”
Section: Functional Outcomementioning
confidence: 99%